Penetapan Titik Pendeteksi Antrian Kendaraan Pada Perempatan Lampu Lalu Lintas - Dian Hartanti; Wisnu Hendro Martono (Sekolah Tinggi Teknik - PLN, 2016)
More dense motor vehicle on the highway will cause a jam. situation where there is accumulation of a motor vehicle was at the time in traffic lights or also called traffic light. Intersection have time to switch the traffic lights that remain in each lane felt less effective because each lane has a different traffic density. Determination of the working area at the intersection of Matraman the survey results for a number of locations in Central Jakarta around each intersection. With data collection for some time with the details of the current condition of the morning, afternoon and evening in every weekday obtained a detailed picture of differences in real conditions. Furthermore, by applying the ISO 7391 (2008) on the specification of street lighting in Urban Area and the rule of PU on the highway, the traffic volume average daily DGH DGH, as well as the use of algorithms Greedy acquired unit quantities dead time live traffic light then can determine the distance sensor placement. From the amount of time living and dead traffic lights can then be developed algorithms and data structures that will be used in the design of software programs intelligent traffic lights